PENGEMBANGAN MEDIA ENSIKLOPEDIA DIGITAL PADA MATERI PENINGGALAN SEJARAH DAN KEBERAGAMAN NUSANTARA SISWA KELAS IV SD - M.Afiz Akhsan Ikhramullah; Siti Halimatus Sakdiyah; Triwahyudianto, Triwahyudianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on innovating educational tools by developing a Encyclopedia-based Digital as an interactive learning medium for the IPAS subject in grade IV elementary school, employing the ADDIE model through its five key stages: Analyze, Design, Development, Implementation, and Evaluation, to create an engaging resource that actively involves students in the learning process. Initial observations and interviews at SDN Sidomulyo 01 Kota Batu revealed that IPAS instruction remains predominantly teacher- centered and relies on conventional media, often resulting in student disinterest and boredom; thus, this new medium integrates elements of a physical interactive book with accessible digital content via Encyclopedia-based Digital to transform traditional lessons into more dynamic and enjoyable experiences. Validation by experts in content, language, and media yielded an average feasibility score of 88,.1%, categorizing it as highly suitable, while implementation feedback indicated strong practicality, with teachers rating it at 90% and students between 88% and 90%, although a full effectiveness evaluation was not completed due to constraints in time and resources. Overall, the Digital Pop-up Book effectively boosts student interest, presents material in a more tangible manner, and fosters an interactive classroom atmosphere, positioning it as an innovative alternative that aligns with 21st-century educational demands and holds potential for broader application in enhancing IPAS teaching quality